Emotional intelligence and innovative teaching behavior of pre-service music teachers: the chain mediating effects of psychological empowerment and career commitment - Jiang, Xin; Tong, Yanli (Frontiers in Psychology, 2025)
IntroductionThis study explores the chain mediating effects of psychological empowerment and career commitment in the relationship between emotional intelligence and innovative teaching behaviors among pre-service music teachers.MethodsA total of 458 pre-service music teachers (Mage = 22.56, SD = 1.97, 26.42% male, 73.58% female) participated in an empirical survey, employing the Emotional Intelligence Scale, Psychological Empowerment Scale, Career Commitment Scale, and Innovative Teaching Behavior Scale. Data analysis was conducted using structural equation modeling (SEM) with SPSS 26.0 and AMOS 24.0 to test the proposed mediation effects.ResultsThe results revealed significant positive relationships between emotional intelligence, psychological empowerment, career commitment, and innovative teaching behaviors. Mediation analysis demonstrated that emotional intelligence influences innovative teaching behaviors through the sequential mediation of psychological empowerment and career commitment.DiscussionThese findings highlight the critical roles of psychological empowerment and career commitment in fostering innovative teaching behaviors. This study offers empirical evidence to enhance the innovative teaching capacities of pre-service music teachers and provides valuable implications for educational practice.